Preserving a Sedekah Bumi Tradition of Munggugianti - Aria Ganna Henryanto; Fitra Muhammad Fauzi; Devi Rahnjen Wijayadne; Farren Ardina; Esfandiani Widyakin; Angelica Satryo; Christian Herdinata (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Culture and society are two things that go hand in hand. Sedekah Bumi is an example of a culture that is preserved by the people of Munggugianti Village who are blessed with fertile land. It has been a tradition that the carnival of the Gunungan Sedekah Bumi must be carried out as a gratitude for God's blessings that have blessed the community's harvest. The existence of such a tradition turns out to be packaged quite interestingly by the surrounding community so that a village can organize a carnival that attracts the attention of the wider community.